A comprehensive analysis of the risk variables linked to HIV infection (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
The current review on factors that makes HIV more likely. Human immunodeficiency is caused by an immunodeficiency virus that targets the host’s T cells. An advanced stage of HIV infection causes AIDS. HIV is a major public health challenge. These review discuss the risk factors for HIV infection, such as frequent sexual partners, unprotected sex, and high-risk sexual behaviours such condom-less anal intercourse. , HIV can be passed from mother to infant during pregnancy and delivery and sharing contaminated needles, syringes, and other injecting equipment, or drug solutions when injecting drugs and connected to transfusion Errors in blood bank procedures, such as contamination during blood collection, processing, or storage, can potentially result in HIV infection. Inflammation of the genital mucosa and the presence of other STIs make women more susceptible to HIV infection through heterosexual vaginal relationships. Getting another STI, such as syphilis, herpes, chlamydia, gonorrhoea, or bacterial vaginosis. And receiving medical procedures that involve unsterile cutting or piercing; or unintentional needle stick injuries, including among healthcare professionals. Another risk factor for HIV infection is socioeconomic status of public.